Fat or thin? A study on the influence of body type of service robots on human-robot interaction willingness - Tu, Yangjun; Hong, Ying; Guan, Dawei; Yang, Zhi (2022 Global Conference on Robotics, Artificial Intelligence and Information Technology (GCRAIT), 2022)
Purpose - Previous research has explored the effect of anthropomorphic service robot appearance (e.g., facial features, humanoid musculoskeletal morphology, etc.) on willingness to use. However, service robots in different service contexts have different body types, and few studies have examined the relationship between different body types and interaction willingness. Therefore, this study aims to investigate which body type (thin vs. fat) can more effectively influence consumers' willingness to interact. Design/methodology/approach - Two experiments were done involving 405 randomly selected online participants using an experimental behavioral method. Study 1 used a one-factor between-subject design (service robot body type: thin vs. fat) to explore the effects of body type on willingness to interact and the mediating mechanism of perceived value. Study 2 used a 2 (body type: thin vs. fat) ×2 (relationship role: companion vs. colleague) between-subjects design to analyze the moderation mechanism. Findings - Study 1 shows that thin service robots increase consumers' perceived value compared to fat service robots, positively influencing consumers' willingness to interact with service robots. Study 2 indicated that participants were more willing to interact with fat (vs. thin) service robots when the service robots played the role of companions (vs. colleagues). Additionally, the moderating effect of the relationship role was also moderated by the relationship strength. The stronger the relationship between the individual and the service robot, the more the service robot as a colleague enhances the individual's willingness to interact with the fat service robot. Originality/value - This study brings implications for the literature on service robot anthropomorphism and the designing of service robots.